1996
DOI: 10.1097/00000658-199611000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Methicillin-Resistant Staphylococcus aureus Bacteremia by Nested Polymerase Chain Reaction

Abstract: ObjectiveThe purpose of this study was to establish a rapid and sensitive diagnostic method for methicillinresistant Staphylococcus aureus (MRSA) bacteremia in postoperative patients. Summary Background DataAs a result of diffusion and abuse of third-generation cephalosporin antibiotics in the 1980s in Japan, an outbreak of MRSA infection has been posed. In the field of surgery, severe postoperative infections with MRSA such as MRSA bacteremia, which may lead to multiple organ failure, have emerged with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A limited study by Kitagawa et al (151) in Japan demonstrated the ability of PCR to directly detect MRSA in clinical specimen. This group developed a nested multiplex PCR for mecA and TSST-1 for use with 1-ml blood samples.…”
Section: Methicillin-resistant Staphylococcimentioning
confidence: 99%
“…A limited study by Kitagawa et al (151) in Japan demonstrated the ability of PCR to directly detect MRSA in clinical specimen. This group developed a nested multiplex PCR for mecA and TSST-1 for use with 1-ml blood samples.…”
Section: Methicillin-resistant Staphylococcimentioning
confidence: 99%
“…Contamination can be controlled using primers designed to anneal at different temperatures. Contamination can also be controlled by adding ultra-pure oil to make a physical separation of two mixtures of amplification [15,17,18]. …”
Section: Nested Pcrmentioning
confidence: 99%
“…The main problems with these systems are the presence of inhibitors and the amplification of non-targets, which can give false negative results (Kasai et al 2000 andStrommenger et al 2003). Detection of MecA gene is also used in many hospitals which can be done by either by radio labeling, PCR amplification or simply by enrichment culture broths (Kitagawa et al 1996).But this method is not very well established as it can only detect nasal and wound infections (Brown et al 2005 andOberdorfer et al2006). Another DNA screening can be done to find the Panton-Valentine leukocidin (PVL) gene, which is also a toxin producer in MRSA infection (Shrestha et al 2002).…”
Section: Introductionmentioning
confidence: 99%